2020
DOI: 10.17263/jlls.851017
|View full text |Cite
|
Sign up to set email alerts
|

L2 motivational self-system as predictors of out-of-class willingness to communicate

Abstract: Empirical studies have long proven the link between speaking and second language learning. Despite its importance in determining one's success to master the target language, willingness to communicate (WTC) is not always high even among motivated and advanced English language learners. This often leads to them not taking the opportunities to engage in verbal activities that are beneficial for them as language learners. The present study seeks to identify the relationship between L2 motivational self-system (th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
3
4
0
Order By: Relevance
“…Also, the Ideal L2 Self perceived by students has a primary role in encouraging their speaking in English with international friends or colleagues. These findings are in line with previous studies (e.g., Dörnyei, 2010;Lee & Lee (2020); Zulkepli (2020); & Kanat-Mutluoğlu's ( 2016)) highlighting the valuable role of the Ideal L2 Self. Similarly, the results reveal that most students have found the ideal L2 Self an effective tool to enhance their speaking during class activities to express themselves.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, the Ideal L2 Self perceived by students has a primary role in encouraging their speaking in English with international friends or colleagues. These findings are in line with previous studies (e.g., Dörnyei, 2010;Lee & Lee (2020); Zulkepli (2020); & Kanat-Mutluoğlu's ( 2016)) highlighting the valuable role of the Ideal L2 Self. Similarly, the results reveal that most students have found the ideal L2 Self an effective tool to enhance their speaking during class activities to express themselves.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, Zulkepli (2020) emphasized that the Ideal Self was the stronger predictor of participants' out-of-class WTC, in line with Kanat-Mutluoğlu's (2016) study, which indicated that the Ideal L2 Self was the best predictor of L2 WTC. Besides, Öz (2016) and Mehmet (2020) conducted studies on Turkish university students majoring in English as a foreign language.…”
Section: Ideal L2 and Wtcsupporting
confidence: 72%
“…This study supports these findings in that participants gave higher ratings to their L2E and WTC when they possessed a more highly developed Ideal Self. The result that higher ratings of the Ideal Self, in particular, predicted WTC ratings supports a link between a more highly developed Ideal Self and WTC, a link also found in several other studies (Joe et al., 2017; Lee & Lu, 2021; Peng, 2015; Zulkepli, 2020). Employing visualization techniques designed to develop the Ideal Self within students in the classroom may be a way programs can help language learners look beyond externally imposed or utilitarian motivations and focus on their personal connection to their TL (Mackay, 2019) while potentially increasing their WTC.…”
Section: Discussionsupporting
confidence: 86%
“…Munezane (2013) was the first researcher who tested the path between the ILS and L2 WTC and approved Dörnyei's (2005) hypothesis. Ever since, various studies have lent further support to the relationship between L2MSS components and L2 WTC (see Munezane, 2015Munezane, , 2016Darling and Chanyoo, 2018;Zulkepli, 2020).…”
Section: L2 Motivational Self-systemmentioning
confidence: 97%